Formulation and resolution of inverse problems for nonlinear, transient structural dynamics - M. Heme, Fram;ois; Doebling, Scott W. (European Journal of Computational Mechanics, 2000)
A general framework is proposed for validating numerical models for nonlinear, transient dynamics. Previous work has focused on nonlinear vibration and several difficulties of formulating and solving inverse problems for nonlinear dynamics have been identified. Among them, we cite the necessity to satisfy continuity of the response when several finite element optimizations are successively carried out and the need to propagate variability throughout the optimization of the model’s parameters. Our approach is illustrated using data from a nonlinear vibration testbed and an impact test experiment both conducted at Los Alamos National Laboratory in support of the advanced strategic computing initiative and our code validation and verification program.